Interindividual variability and lateralization of mu-opioid receptors in the human brain - Kantonen Tatu; Karjalainen Tomi; Isojärvi Janne; Nuutila Pirjo; Tuisku Jouni; Rinne Juha; Hietala Jarmo; Kaasinen Valtteri; Kalliokoski Kari; Scheinin Harry; Hirvonen Jussi; Vehtari Aki; et al. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Alterations in the brain's mu-opioid receptor (MOR) system have been associated with several neuropsychiatric disorders. Central MOR availability also varies considerably in healthy individuals. Multiple epidemiological factors have been proposed to influence the MOR system, but due to small sample sizes the magnitude of their influence remains inconclusive. We compiled [C-11] carfentanil positron emission tomography scans from 204 individuals with no neurologic or psychiatric disorders, and estimated the effects of sex, age, body mass index (BMI) and smoking on [C-11]carfentanil binding potential using between-subject regression analysis. We also examined hemispheric differences in MOR availability. Older age was associated with increase in MOR availability in frontotemporal areas but decrease in amygdala, thalamus, and nucleus accumbens. The age-dependent increase was stronger in males. MOR availability was globally lowered in smokers but independent of BMI. Finally, MOR availability was higher in the right versus the left hemisphere. The presently observed variation in MOR availability may explain why some individuals are prone to develop MOR-linked pathological states, such as chronic pain or psychiatric disorders. Lateralized MOR system may reflect hemispheric work specialization in central emotion and pain processes.